Giant Magnetoresistance: Basic Concepts, Microstructure, Magnetic Interactions and Applications - Inga Ennen; Daniel Kappe; Thomas Rempel; Claudia Glenske; Andreas Hütten (Sensors, 2016)
The giant magnetoresistance (GMR) effect is a very basic phenomenon that occurs in magnetic materials ranging from nanoparticles over multilayered thin films to permanent magnets. In this contribution, we first focus on the links between effect characteristic and underlying microstructure. Thereafter, we discuss design criteria for GMR-sensor applications covering automotive, biosensors as well as nanoparticular sensors.